Antibiotic Use in Inpatients with Diarrhea in Children: A Quantitative Evaluation at Hospital X, Semarang Regency, 2023 - Widiastuti, Zulfia; Purwaningsih, Avianti Eka Dewi Aditya; Ulum, Amalia Nurul (Jurnal FARMASIMED (JFM), 2025)
Background : Infection remain one of the leading causes of morbidity in tropical regions such as Indonesia, with Escherichia coli being one of the most freequently identified pathogens. The high incidence of Escherichia coli-related infections has led to increased antibiotics use, considering that this commensal gut bactericum can cause both asymptomatic infections and symtomatic diarrhe, either bloody or non-bloody. Objective : This study aimed to evaluate use in pediatric patiens with diarrea at Hospital X, Semarang Regency, in 2023. Methods: This was a retrospective study uutilizing medical records of 323 pediatric patiens who met the inclusion and exclusion criteria. Data analysis was performed using the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) methodology. Result:The analysis revealed that Ceftriaxone injection was the most frequently used antibiotic (61.95%), followed by Ampicillin, Amikacin, Gentamicin, and Cefotaxime. Ceftriaxone was often prefered due to its efficacy against both gram-positive and gram-negative bacteria comonly associated with pediatric diarrhea, as well as the advantage of accurate dosing trough injectable formulations. Most diarrhea cases occurred in boys (62.54%) and in children under five years of age (65.63%). Conclusion:Injectable formulations were chosen to reduce the risk of vomiting and to facilitate precise and effective dosing. Evaluation using the ATX/DDD method highlighted the need for more rational antibiotic management to prevent bacterial resistance in the future. Optimizing antibiotic stewardship is crucial to ensure targeted in the future. Optimizing antibiotic stewardship is crucial to ensure targeted, effective use and to preserve therapeutic efficacy in the long term.